Stimulated echo diffusion tensor imaging and SPAIR T2‐weighted imaging in chronic exertional compartment syndrome of the lower leg muscles. Issue 5 (25th February 2013) - Sigmund, Eric E.; Sui, Dabang; Ukpebor, Obehi; Baete, Steven; Fieremans, Els; Babb, James S.; Mechlin, Michael; Liu, Kecheng; Kwon, Jane; Mcgorty, KellyAnne; Hodnett, Philip A.; Bencardino, Jenny
Abstract : Purpose: To evaluate the performance of diffusion tensor imaging (DTI) in the evaluation of chronic exertional compartment syndrome (CECS) as compared to T2 ‐weighted (T2w) imaging. Materials and Methods: Using an Institutional Review Board (IRB)‐approved, Health Insurance Portability and Accountability Act (HIPAA)‐compliant protocol, spectral adiabatic inversion recovery (SPAIR) T2w imaging and stimulated echo DTI were applied to eight healthy volunteers and 14 suspected CECS patients before and after exertion. Longitudinal and transverse diffusion eigenvalues, mean diffusivity (MD), and fractional anisotropy (FA) were measured in seven calf muscle compartments, which in patients were classified by their response on T2w: normal (<20% change), and CECS (>20% change). Mixed model analysis of variance compared subject groups and compartments in terms of response factors (post/pre‐exercise ratios) of DTI parameters. Results: All diffusivities significantly increased ( P < 0.0001) and FA decreased ( P = 0.0014) with exercise. Longitudinal diffusion responses were significantly smaller than transversal diffusion responses ( P < 0.0001). Nineteen of 98 patient compartments were classified as CECS on T2w. MD increased by 3.8 ± 3.4% (volunteer), 7.4 ± 4.2% (normal), and 9.1 ± 7.0% (CECS) with exercise. Conclusion: DTI shows promise as an ancillary imaging method in the diagnosis and understanding of the pathophysiology in CECS. Future studies may explore its utility in predicting response to treatment. J. Magn. Reson. Imaging 2013;38:1073–1082. © 2013 Wiley Periodicals, Inc.